2011
DOI: 10.1007/s00595-010-4437-3
|View full text |Cite
|
Sign up to set email alerts
|

Management of ABO-incompatible living-donor liver transplantation: Past and present trends

Abstract: Based on the concept that the liver is a "privileged organ," which resists acute rejection, Thomas Starzl introduced liver transplantation across the ABO blood group. However, with improved survival after liver transplantation came reports of an increased incidence of acute rejection, biliary and vascular complications, and decreased survival after ABO-incompatible liver transplantation. As a result, ABO-incompatible liver transplantations are performed only in emergencies when ABO-compatible grafts are unavai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 23 publications
0
66
0
Order By: Relevance
“…Even though the role of the ABO antibody titer is still not well defined, the general belief is that a higher IA titer may result in a higher risk of AMR (4)(5)(6)17,26).The role of IA titers in the AMR of ABOi LT has been controversial. Mor et al (38) showed a possible link between a high IA titer and AMR, in particular, in A-to-O transplants, whereas Skogsberg et al (39) showed no correlation between a high IA titer and AMR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the role of the ABO antibody titer is still not well defined, the general belief is that a higher IA titer may result in a higher risk of AMR (4)(5)(6)17,26).The role of IA titers in the AMR of ABOi LT has been controversial. Mor et al (38) showed a possible link between a high IA titer and AMR, in particular, in A-to-O transplants, whereas Skogsberg et al (39) showed no correlation between a high IA titer and AMR.…”
Section: Discussionmentioning
confidence: 99%
“…Most deaths in the earlier experiences of ABOi LT were associated with AMR or infections caused by inefficacious overimmunosuppression. Consequently, ABOi LT became unpopular and was reserved for urgent LT, particularly for pediatric patients (4). Since the introduction of desensitization (DSZ) with the anti-CD20 monoclonal antibody rituximab (RIT), the risk of hepatic necrosis caused by full-blown AMR has almost disappeared, and overimmunosuppression aimed at avoiding AMR is no longer required (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies had reported increased risk of humoral and cellular rejection, arterial thrombosis and biliary complications after ABO incompatible liver transplants (ABOiLT) [53] . Measures such as peri-operative plasmapheresis [54] , and rituximab [55] have been used to lower peri-operative recipient antibody levels and thereby decrease the risk of these complications.…”
Section: Abo Incompatible Liver Transplantsmentioning
confidence: 99%
“…The catheter was placed through one of the branches of the hepatic artery after anastomosis. This protocol improved the 1-year survival after ABO-I LDLT to 85%, and decreased the frequency of portal vein thrombosis [25]. However, severe bleeding could occur if the catheter dislocates, either spontaneously or during its removal.…”
Section: Mechanism Of Abo Blood Type Related Rejectionmentioning
confidence: 99%
“…However, these days, the clinical significance of splenectomy has become a matter of controversy. The spleen represents only around a quarter of the peripheral lymphoid tissue, and splenectomy compromises the immune response because the recipient is deprived of the other immune functions of the spleen and is at an increased risk of infections [25]. The Kyoto group recently reported that there was no statistically significant difference in anti-ABO immunoglobulin M and immunoglobulin G antibody titers between the "splenectomy" and "nonsplenectomy" groups during the initial 8 weeks [29].…”
Section: Splenectomymentioning
confidence: 99%